Diurnal decline in photosynthesis and stomatal conductance in several tropical species - Suwannarut, Wachira; Vialet-Chabrand, Silvere; Kaiser, Elias (Frontiers in Plant Science, 2023)
Photosynthesis (A) and stomatal conductance (gs) change diurnally due to internal signals, but the effects of diurnal rhythms on dynamic photosynthetic behavior are understudied. We examined diurnal changes in A and gs in ten tropical species: across species, there was a tendency for A and gs to decline diurnally when these were repeatedly measured under either steady-state or fluctuating irradiance conditions. We then examined in more detail the irradiance-induced kinetics of gas exchange in a C3 and C4 crop species each, namely fig (Ficus carica) and sugarcane (Saccharum officinarum). During the day, fig showed significantly slower photosynthetic induction and lower gs, as well as a slower gs increase, in the afternoon than in the morning and noon. Sugarcane showed a reduction in steady-state A reached under high irradiance and slower gs increase as well as lower gs reached under high irradiance, but no changes in the rate of photosynthetic induction, in the afternoon, compared to morning and noon. These reductions in the afternoon were not reverted by a dark treatment in the middle of the day, suggesting that the decrease was not proportional to diurnal time-integrated carbon fixation. Repeated exposure to light- and shadeflecks (1000 and 50 μmol m-2 s-1, lasting 20 min each) revealed fundamental differences in stomatal regulation between species: in fig, stomata opened and closed slowly, and their opening became progressively slower under a series of lightflecks, whereas sugarcane showed much faster stomatal opening than closure that was unchanged during the course of the day. Our results highlight that steady-state rates and irradiance-induced kinetics of photosynthesis and stomatal movement change diurnally in most species studied, and that they do so differently in fig and sugarcane.